Analysing Child Paternity Cases through the Lens of Maqasid Sharia: A Case Study of Judicial Rulings - Sunarto, Muhammad Zainuddin; Imani, Nur Diana (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2025)
This study aims to analyze the application of Maqasid Syariah principles in religious court decisions related to child paternity cases, with a focus on Decision Number 123/Pdt.P/2024/PA. Prob. This research is motivated by the importance of protecting the nasab and rights of children in Islamic family law, as well as the need to understand how Indonesia's positive law can accommodate sharia values in the context of the family. This study uses a qualitative method with a type of empirical juridical research that focuses on field research. Data was obtained through interviews with related parties, observation of the trial process, and analysis of court decision documents. The findings show that the religious court's decision to reject part of the application in this case has reflected efforts to uphold the principle of hifz al-nasl (protection of offspring), but there are some inconsistencies in the application of hifz al-mal (protection of property) regarding the distribution of inheritance and protection of guardians of children. The findings are expected to provide new insights into how the principles of Maqasid Syariah can be integrated into the Indonesian legal system, as well as the importance of adjustments in the application of the law to better accommodate the rights of children and families based on Islamic teachings.